Scale to Measure Public attitude towards Police: Measuring Public Attitudes towards Police using a Developed Scale (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the developing society it’s also important to understand the most required function the protection and safeguarding and up keeping the law and order of the state and country therefore it’s important to understand the public attitude towards police, police generally is considered to be most called, approached and trusted for every social and personal problems of the society and individual. The aim of the present study was to develop a scale to measure this variable. A group of 5 researchers generated 105 items across various dimensions. These items were submitted to subject experts for suggestions and advice, based on which certain items were removed or altered. The final scale consisted of 32 items. The scale was administered to the sample of 520 working class people and postgraduate students, consisting of 260 males and 260 females. The reliability test was done using SPSS V21 software. The Cronbach’s alpha was found to be .789,The reliability statistics for public attitude towards police in 2 dimensions i.e., in positive dimension the cronbach’s was found to be .854,in negative dimension the cronbach’s alpha was found to be .783, The mean was found to be 90. Norms were formulated based on the analysis. Subjects who score more than 90 are interpreted as having positive attitude towards police and subjects who score less than 90 are interpreted as having negative attitude towards police. The researcher individually analysed gender differences, using a t-test. It was found out that there is a significant difference in public attitude towards police between male and female, Female have more positive attitude towards police than the male.